FORMALNOŚĆ ROZWODU W RZYMSKIM PRAWIE KLASYCZNYM: D. 24,2,9 I AUGUSTOWSKIE DIVORTIIS MODUM IMPONERE - Urbanik, Jakub (Zeszyty Prawnicze, 2017)
The Formality of Divorce under the Classical Roman Law: D. 24.2.9 and Augustean DIVORTIIS MODUM IMPONERE Summary The present article critically reexamines the classical sources on divorce. The key text, D. 24,2,9, Paul’s commentary on Julian Law on Adulteries is confronted with the fragments in which the jurisprudence addressed the troublesome issue of establishing the moment of real divorce (D. 24,1,64; 25,2,11 pr.; 23,2,33 & Frag.Vat. 106-107). The traditional scholarship (P. Bonfante, G. Longo, S. Solazzi, E. Volterra, O. Robleda, J. Huber) is evaluated, with a particularly critical approach to the most recent studies of R. Astolfi. In the second part, the sources, prima facie, deposing in favour of the general application the divorce procedure in D. 24,2,9, are taken into consideration (D. 24,1,35; 38,1,11 and D. 48,5,44/43/). A new interpretation is presented in regards to the vexed problem of legitima observatio in D. 24,1,35. Finally, a duplex interpretatio is postulated for the seven-witness procedure found at D. 24,2,9. This hypothesis seems to provide for the better understanding of the text collocation in the general title de divortiis of the Digest.